2017
DOI: 10.6061/clinics/2017(07)05
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D in patients undergoing kidney transplant: the importance of sunlight exposure

Abstract: OBJECTIVES:Recent studies have shown a high prevalence of hypovitaminosis D, defined as a serum 25-hydroxyvitamin D level less than 30 ng/ml, in both healthy populations and patients with chronic kidney disease. Patients undergoing kidney transplant are at an increased risk of skin cancer and are advised to avoid sunlight exposure. Therefore, these patients might share two major risk factors for hypovitaminosis D: chronic kidney disease and low sunlight exposure. This paper describes the prevalence and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Vitamin D deficiency is prevalent among patients with chronic renal disease (CKD) treated conservatively or with dialysis, and among kidney-transplanted patients ( 104 , 105 ). A meta-analysis with more than 17,000 patients concluded that hypovitaminosis D was associated with an increased risk of all-cause mortality, especially in patients undergoing dialysis.…”
Section: Which Conditions Could Benefit From 25(oh)d Concentrations A...mentioning
confidence: 99%
“…Vitamin D deficiency is prevalent among patients with chronic renal disease (CKD) treated conservatively or with dialysis, and among kidney-transplanted patients ( 104 , 105 ). A meta-analysis with more than 17,000 patients concluded that hypovitaminosis D was associated with an increased risk of all-cause mortality, especially in patients undergoing dialysis.…”
Section: Which Conditions Could Benefit From 25(oh)d Concentrations A...mentioning
confidence: 99%
“…The study design was cross-sectional in 27 studies [ 11 , 12 , 14 , 15 , 18 21 , 23 32 , 34 – 37 , 41 45 ] (71.1%) and longitudinal in 11 [ 13 , 16 , 17 , 22 , 33 , 38 40 , 46 48 ] (28.9%). All these articles were published between 2001 and 2021, and most of them were conducted in Europe [ 13 , 14 , 16 , 19 24 , 29 – 31 , 35 , 36 , 38 , 39 , 42 ] (44.7%), although there were also studies from Asia [ 11 , 18 , 25 27 , 34 , 37 , 40 , 43 , 45 , 46 , 48 ] (31.6%), America [ 15 , 17 , 28 , 32 , 33 , 44 , 47 ] (18.4%) and Oceania [ 12 , 41 ] (5.3%).…”
Section: Resultsmentioning
confidence: 99%
“…The overall prevalence was 29.8% (95% CI: 23.8-36.7; I 2 = 96.8) (Supplementary Figure S13). (e) Hypovitaminosis D: Eight studies [14,19,31,37,[42][43][44][45] analysed the prevalence of this disorder. In this population of 2,495 people, the overall prevalence was 81.8% (95% CI: 67.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation